Indigenous Microorganisms Offset Arbuscular Mycorrhizal Fungi-Induced Plant Growth and Nutrient Acquisition Through Negatively Modulating the Genes of Phosphorus Transport and Nitrogen Assimilation - Ren, Wenda; Guo, Yun; Han, Xu; Sun, Yan; Li, Qing; Wu, Bangli; Xia, Tingting; Shen, Kaiping; Wu, Pan; He, Yuejun (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal (AM) fungi that promote plant growth and nutrient acquisition are essential for nutrient-deficient karst areas, while they inevitably regulate host plants jointly with indigenous microorganisms in natural soil. However, how indigenous microorganisms regulate AM-induced benefits on plant growth and nutrient acquisition remains unclear. In this study, the Bidens tripartita as the common plant species in the karst region was cultivated into three soil substrates treated by AM fungi inoculation (AMF), AM fungi inoculation combining with indigenous microorganisms (AMI), and the control without AM fungi and indigenous microorganisms (CK). The plant biomass and concentration of nitrogen (N) and phosphorus (P) were measured, and the transcriptomic analysis was carried out using root tissues. The results showed that AM fungi significantly enhanced the plant biomass, N, and P accumulation with the reduction of plants’ N/P ratio; however, the indigenous microorganisms offset the AM-induced benefits in biomass and N and P acquisition. In addition, there are 819 genes in differentially expressed genes (DEGs) of AMF vs. AMI ∩ AMF vs. CK, meaning that AM fungi induced these genes that were simultaneously regulated by indigenous microorganisms. Furthermore, the enrichment analysis suggested that these genes were significantly associated with the metabolic processes of organophosphate, P, sulfur, N, and arginine biosynthesis. Notably, 34 and 17 genes of DEGs were related to P and N metabolism, respectively. Moreover, the indigenous microorganisms significantly downregulated these DEGs, especially those encoding the PHO1 P transporters and the glnA, glutamate dehydrogenase 2 (GDH2), and urease as key enzymes in N assimilation; however, the indigenous microorganisms significantly upregulated genes encoding PHO84 inducing cellular response to phosphate (Pi) starvation. These regulations indicated that indigenous microorganisms restrained the N and P metabolism induced by AM fungi. In conclusion, we suggested that indigenous microorganisms offset nutrient benefits of AM fungi for host plants through regulating these genes related to P transport and N assimilation.